Not All Events Are Attended Equally: Toward a Middle-Range Theory of Industry Attention to External Events - Hoffman, Andrew J.; Ocasio, William (Organization Science, 2001)
This paper builds on prior theory and research on attention and identity to examine whether and how industries publicly attend to external events. Events are critical triggers of institutional transformation and industry evolution. However, they must first become the focus of public attention to have this effect. We draw on a paired case comparison of media coverage of eight nonroutine events affecting the natural environment and the U.S. chemical industry. We employ both deductive and inductive analysis to develop a model and hypotheses to explain two research questions. First, what determines the initial public attention to an event? Second, when and why do certain events attain high and sustained levels of industry attention? A key inference is that whether an event receives industry-level attention depends on either outsiders holding the industry accountable for the event, or insiders' internal concerns with the industry image. We further infer that an event can be transformed into a critical issue for an industry, warranting sustained attention, if there is contestation with outsiders over the accountability for the event and its enactment, and internal contradictions and challenges to the industry's identity.